An Overview of Data Analysis of EMR, Its Clinical Ontologies & Security in Database with respect to Todays Ehealth Apps - Kemkar, Onkar S; Dahikar, Dr P B (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The convergence of the information and communication technology (ICT) has produced many exciting possibilities for developing new services in medical field for the citizens. Electronic medical records (EMRs) are used in large healthcare centers to increase efficiency and accuracy of documentation. These databases may be utilized for clinical research or to describe clinical practices such as medication usage. The paper discusses an overview of the features and functions of major electronic health records (EHR) and reviews how they are being used in academic medical centers (AMC) AMCs were among the pioneers in developing automated EHRs, is the available ICT technology is suitably modified and used for experimentation, vocabularies and interfaces appropriate for clinical trial research